(untitled) (KULT_online, 2014)
Which method is right for learning a foreign language? This central question in foreign-language teaching is treated in an understandable and clear way by Dietmar Röslers "Deutsch als Fremdsprache. Eine Einführung". In the book the discussion is presented in its historical development and with all its controversy, and the current state of research is reported upon. The introduction covers almost the whole range of relevant topics and provides a good overview for students of German as a foreign language.